Implementation of an improvement cycle in the care of a primary health care - Tainara Barbosa Nunes; Éricka Cecília Resende de Souza; Zenewton André da Silva Gama; Wilton Rodrigues Medeiros; Ana Elza Oliveira de Mendonça (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to evaluate the effectiveness of a quality improvement cycle applied to the care of spontaneous demand in a primary care center. Methods: quasi-experimental before and after study, with a quantitative approach and no control group. An improvement cycle was carried out in a primary care center in the city of Guarabira/PB using five quality criteria. An evaluation, an intervention focused on the most problematic criterion and a reassessment were carried out. The samples were random (n = 60). The percentages and confidence intervals of compliance with each criterion were verified. Statistical significance was calculated using the Z test. Results: after the intervention, there was a significant improvement in two quality criteria of the care of spontaneous demand users (the user must be heard by a professional and go through the risk classification). Conclusions: the improvement cycle was an effective quality management method.